Karakteristik hipertensi pada anak di Instalasi Rawat Inap (IRNA) RSUP Sanglah, Bali, Indonesia - Desak Made Widiastiti Arga; I Ketut Suarta; Gusti Ayu Putu Nilawati (DiscoverSys Inc., 2020)
Background: The prevalence of hypertension in children and adolescents has increased in the last decade. Hypertension in children is associated with hypertension in adults that have not been treated well and one of the risk factors for cardiovascular disease, kidney disease, and other organ damage. Data on hypertension in children is still limited, especially in Indonesia. This study aims to determine the characteristics of children with hypertension in the inpatient installation of Sanglah Hospital Denpasar.Methods: This is a retrospective cross-sectional study with a descriptive design. Data were collected from pediatric patients' medical records age 1-18 years old diagnosed with hypertension in 2018-2019. Variables assessed in this study were gender, age, etiology of hypertension, symptoms, and number of antihypertensive therapies. Data were analyzed using SPSS version 22 for Windows.Results: A total of 56 children with hypertension were included in this study. Subjects were dominated by the female (53.6%), ages 6-13 years (46.4%) with a median age of 11 years, and well-nourished (46.4%). The etiology of hypertension for all subjects is secondary hypertension, mostly caused by kidney disease (75%). Hypertension symptoms are generally not specific; headache is the most common symptom of hypertensive crisis (35.7%). Stage 2 hypertension is most common in this study (57.1%); hypertensive crises mostly occur in children aged ?13 years and are treated in the intensive care unit. Children with stage 2 hypertension and hypertensive crisis tend to show uncontrolled hypertension upon hospital discharge (44.4%). The majority of children received single antihypertensive therapy (51.8%).Conclusion: The etiology of hypertension in children is mostly secondary hypertension caused by kidney disease. Second-degree hypertension is the most common hypertension in children who are treated with hypertension. The outcome is mainly controlled hypertension with single antihypertensive therapy. Latar belakang: Angka kejadian hipertensi pada anak dan remaja mengalami peningkatan dalam dekade terakhir. Hipertensi pada anak erat kaitannya dengan kejadian hipertensi pada dewasa yang tidak ditata laksana dengan baik, dan salah satu faktor risiko timbulnya penyakit kardiovaskuler, ginjal dan kerusakan organ lain. Data mengenai hipertensi pada anak masih terbatas terutama di Indonesia. Penelitian ini bertujuan untuk mengetahui karakteristik hipertensi pada anak di Instalasi Rawat Inap RSUP Sanglah Denpasar.Metode: Penelitian ini merupakan penelitian potong lintang retrospektif menggunakan rancangan deskriptif. Data diambil dari rekam medis pasien anak berusia 1-18 tahun yang dirawat dengan hipertensi pada tahun 2018-2019. Variabel yang dinilai pada penelitian ini adalah Jenis kelamin, usia, etiologi hipertensi, gejala, dan jumlah obat anti hipertensi. Data dianalisis dengan SPSS versi 22 untuk Windows.Hasil: Sebanyak 56 anak dengan hipertensi diikutkan dalam penelitian ini. Subjek didominasi oleh jenis kelamin perempuan (53,6%), usia 6-13 tahun (46,4%) dengan median usia 11 tahun, dan gizi baik (46,4%). Etiologi hipertensi seluruh subjek adalah hipertensi sekunder yang paling banyak disebabkan oleh penyakit ginjal (75%). Gejala hipertensi secara umum tidak spesifik; sakit kapala merupakan gejala yang paling sering dikeluhkan pada krisis hipertensi (35,7%). Hipertensi derajat 2 paling banyak ditemukan pada subjek (57,1%); krisis hipertensi sebagian besar terjadi pada anak berusia ?13 tahun dan dirawat di ruang intensif. Anak dengan hipertensi derajat 2 dan krisis hipertensi cenderung menunjukkan hipertensi yang tidak terkontrol saat keluar rumah sakit (44,4%). Mayoritas anak mendapatkan terapi antihipertensi tunggal (51,8%).Kesimpulan: Hipertensi pada anak mayoritas adalah hipertensi sekunder yang disebabkan oleh penyakit ginjal. Hipertensi derajat 2 adalah hipertensi yang paling banyak ditemukan pada anak yang dirawat dengan hipertensi. Sebagian besar memiliki luaran hipertensi yang terkontrol dengan terapi antihipertensi tunggal.